2001
DOI: 10.1177/1532673x01029006005
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Ballot Initiatives on Voter Turnout in the American States

Abstract: With few exceptions, voter turnout continues to decline in the United States. Although normative theorists, journalists, and defenders of participatory democracy frequently suggest that citizeninitiated ballot measures can increase voter turnout, previous research has not supported this claim. Yet, in the past 25 years, usage of direct democracy has exploded in the United States. Using pooled time series data for the 50 states over a 26-year period (1970-1996), we find that the presence and usage of the initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
103
3

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 151 publications
(116 citation statements)
references
References 29 publications
8
103
3
Order By: Relevance
“…Research examining the impact of direct democracy on citizen participation over the past twenty-five years finds that states with frequent use of ballot initiatives have higher voter turnout rates. 25 Because voters can directly adopt policy, one might expect that citizens living in initiative states should perceive government as more responsive; thus, a potential consequence of direct democracy concerns political efficacy. But there is little empirical research addressing the question of initiatives and citizen attitudes towards government, particularly regarding efficacy, in the United States.…”
mentioning
confidence: 99%
“…Research examining the impact of direct democracy on citizen participation over the past twenty-five years finds that states with frequent use of ballot initiatives have higher voter turnout rates. 25 Because voters can directly adopt policy, one might expect that citizens living in initiative states should perceive government as more responsive; thus, a potential consequence of direct democracy concerns political efficacy. But there is little empirical research addressing the question of initiatives and citizen attitudes towards government, particularly regarding efficacy, in the United States.…”
mentioning
confidence: 99%
“…Given that we do not account for the salience of initiatives, but rather only whether the state allows for initiatives, this likely creates a bias against obtaining significant results. Furthermore, Tolbert, Grummel, and Smith (2001) find that the presence of initiatives alone is associated with an increase in state-level turnout for national offices, which could further decrease the likelihood that we would find significant results, given the construction of our dependent variables. It is worth noting also that other studies have demonstrated that the presence of an initiative (e.g., Boehmke 2005; Gerber 1999) can have indirect effects on political actions and outcomes.…”
Section: Additional Testsmentioning
confidence: 83%
“…Early research in the US context has only found scant evidence that the presence of direct democratic procedures in US states boosts election turnout [10,11]. More recent research, however, indicates that direct democracy might indeed have a positive effect on election turnout [12,13]. This mobilizing effect in the US is stronger for mid-term elections than for presidential elections [14].…”
Section: Direct Democracy and Voter Mobilizationmentioning
confidence: 96%